18F-FDG PET/CT for Staging and Response Evaluation in a Rare Case of Childhood Ovarian Primitive Neuroectodermal Tumor. (May 2021) - Sharma, Punit; Ghosh, Indranil; Khan, Enam Murshed
Abstract : Abstract: Primitive neuroectodermal tumor (PNET) is an aggressive small cell malignancy. Apart from the central nervous system, they can arise from peripheral sites as well. Ovarian PNETs are extremely rare neoplasms. We here present a case of childhood ovarian PNET, where 18 F-FDG PET/CT was efficiently used for staging and response evaluation.